Framing Global Racism Locally: Agenda-Setting of GeorgeFloyd’s Death in Indonesia’s Analisa Daily - Abdul Rani Usman; Azman Sulaiman; Julianto Saleh; Mira Fauziah; Muslim Muslim; Fachrur Rizha (Jurnal Ilmiah Peuradeun, 2026)
This study examined how global racial injustice was constructed and prioritized within local media through agenda-setting mechanisms, focusing on Analisa Daily’s coverage of George Floyd’s death in the United States. Drawing on Agenda-Setting Media Theory, particularly the unification of agenda approach, the study employed a qualitative interpretive content analysis of international news reports published in Analisa Daily between June 2 and 23, 2020. The findings revealed that the newspaper sets a coherent agenda on racism by consistently foregrounding structural–historical continuity, political–ideological contradiction, and discursive–global framing. Rather than portraying racism as an isolated incident, Analisa Daily constructed it as a systemic problem embedded in institutional history, electoral politics, and transnational legitimacy struggles. The study further demonstrated that Indonesian print media did not merely replicate Western news agendas but actively aligned, reframed, and evaluated global racial narratives through selective emphasis and normative interpretation. By empirically showing how global racial injustice was localized and unified within a Global South media context, this research advanced agenda-setting scholarship beyond issue salience toward transnational meaning-making and legitimacy contestation. The findings underscore the role of local media as active mediators in shaping global human rights discourse rather than passive recipients of dominant Western narratives.